ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN DALAM MEMBELI IKAN SEGAR (STUDI KASUS DI PASAR SEHAT SOREANG KABUPATEN BANDUNG) - Hakim, Amara Rohullah Balqish; Nurhayati, Atikah; Dewanti, Lantun Paradhita; Maulina, Ine (Universitas Pattimura, 2024)
The fish production figure in Bandung District is 32,167 tons with per capita fish consumption of 20.5 kilograms. This amount is still much lower than the national fish consumption of 47.34 kilograms and much lower than the total annual fish consumption figure for West Java Province of 38.23 kilograms. Even though fish contains protein in the range of 15-24% and is equipped with essential amino acids which reach 95%. The aim of this research is to analyze the factors that influence consumer preferences in buying fresh fish at the Soreang Sehat Market. The research was carried out from October 2023 to January 2024. The research location was the Soreang Sehat Market, Bandung Regency, West Java. The method used in this research is a case study. Data analysis used Minitab 16.0 for Windows software. The location of the research was at the Soreang Sehat Market, Bandung District. The data used is primary data and secondary data. The primary data collection technique used Accidental Sampling with a sample of 100 respondents. In this study, the variables studied were divided into 4 groups, namely the independent variables consisting of fish freshness factors (X1), consumer personal factors (X2), consumer psychological factors (X3) consumer social factors (X4), and the dependent variable, namely preferences. consumer (Y). The research instrument used was a questionnaire and to obtain quantitative data a 5 point likert scale model was used. The results of this research show that based on the multiple regression test, the R-square value is 78.40%, which means that 78.40% of the factors in this research influence consumer preferences in buying fresh fish.